Economic Law Creation Beautiful Global Indonesia - Liana Endah Susanti (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2019)
Indonesia is the world 's largest archipelago with 1,904,569 km2 of surface area. A very diverse landscape with a variety of abundance of flora and fauna is a special attraction for foreign tourists. Not only that, the natural wealth in Indonesia 's intestines is also very abundant, as are various minerals and richness from other mining materials. However, a abundance of skilled human capital, both in terms of science and technology mastered, do not complement the plentiful natural resources. This is one of the reasons superpowers should be providing cooperation. PT. PT. Freeport is an clear example of Indonesia 's collaboration in the mining sector with foreign parties. The first contract for Freeport-Indonesia was established in 1967. After the Foreign Investment Law was passed in 1967, Freeport became the first foreign mining firm to operate in Indonesia. But the existence of this partnership was regretted by many because it was perceived to be detrimental to the region. The reason is that so far nobody knows for sure how much gold and silver has been produced from the mining to date. The magnitude of the distribution of mining goods is also not quite good given that Indonesia owns land which is turned into gold fields. There are, in fact, many reports uncovering miserable stories of discrimination by indigenous people around the mining region. Justice is once again present as something that is not only wishful thinking, but also noble values that have to be realized for the collective good of the state goals set out in the Pancasila points and the preamble to the Constitution of 1945. Keywords: Mining, PT. Freeport, Discrimination, justice